Facts, opinions, and media spectacle: Exploring representations of business news on the internet - Tan, Sabine (Sage Publications Ltd, 2011)
In the 21st century, the field of business and finance has become a media spectacle. Not only have advances in technology changed the ways in which audiences engage with business information, the pervasiveness of internet and cable television networks has led to the emergence of new hybrid forms of business news discourse, blending verbiage, images, graphics, audio, and video clips. Combining discourse analysis, social semiotic theory, and other interdisciplinary approaches, this article explores the multiple ways in which business news are mediated on the internet by continuous 24-hour business news networks such as Bloomberg, CNBC, FOXBusiness, and Reuters. In particular, this article is concerned with how events are contextualized, that is, how identities and social relationships are constructed and represented within and across different modes, media, and networks. The analysis focuses on what is foregrounded or backgrounded, what is thematized or unthematized in each mode and medium, and what process types and categories are drawn upon to represent events, social actors, and social (inter)actions. In this context, special interest is being paid to the semiotic shifts or transformations (and ensuing re-contextualizations) that multimodal representations undergo across modes, media, and news networks.